Effect of lap configuration on magnesium to aluminum friction stir lap welding assisted by external stationary shoulder - Ji, Shude; Li, Zhengwei; Zhang, Liguo; Zhou, Zhenlu; Chai, Peng (Materials & design, 2016)
In the present study, friction stir lap welding (FSLW) assisted by external stationary shoulder was firstly used to weld magnesium to aluminum alloys. Effects of the assisted stationary shoulder on joint surface appearances, cross-sections, microstructure and mechanical properties were mainly studied. Lap joints using different lap configurations were also discussed. Results show that lap joints with smooth surface and very small flash can be obtained by the assisted stationary shoulder. When using different sheet configurations, joint cross-section morphologies and microstructure changed significantly. The main intermetallic compounds (IMC) formed in the stir zone (SZ) boundary on the Al/Mg joint is Al12Mg17. The main IMC formed in the Mg/Al joint SZ is Al3Mg2. With increasing the welding distance, tunnel defect appears in the Al/Mg joint. Lap shear failure load of the Mg/Al joints are much bigger than that of the Al/Mg joints. All the lap joints present shear failure and dimples can be observed on all joints. [Display omitted] •Stationary shoulder technology is firstly used in friction stir lap welding of aluminum to magnesium alloys.•The external stationary shoulder exerts a big forging force on the joint, which is beneficial to joint formation.•The stationary shoulder significantly increases the bonding area of the lap joint.•Lap joint, which aluminum alloy was placed as the upper sheet, was studied.•With increasing the welding distance, serious tunnel defect can be observed in the Al/Mg joint.